2019
DOI: 10.1002/smtd.201900041
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Proteomics in Novel PTM Discovery: Applications in Cancer Therapy

Abstract: Protein posttranslational modification (PTM) is a critical mechanism to enhance the diversity of protein species and functions in organisms. Currently, many different PTMs are discovered and found to be involved in a wide range of cellular processes. The aberrant regulation of PTM dynamics is reported to contribute to cancer development. Phosphorylation and acetylation are the best studied PTMs, and the application of high‐resolution mass spectrometry‐based proteomics and specific antibody‐based enrichment tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 107 publications
0
24
0
Order By: Relevance
“…Protein post-translational modifications (PTMs), the covalent processing events that cleaving or adding a modifying group to an amino acid or more amino acids, are essential regulatory patterns of diverse biological processes and cellular events [1]. Increasing new PTMs have been reported due to the development of high-resolution mass spectrometry (MS), such as acetylation (Kac), succinylation (Ksucc), propionylation, butyrylation and crotonylation etc [2][3][4]. With bioinformatics tools, their biological processes regulation and metabolic pathways adjustment roles have been illustrated to some extent [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein post-translational modifications (PTMs), the covalent processing events that cleaving or adding a modifying group to an amino acid or more amino acids, are essential regulatory patterns of diverse biological processes and cellular events [1]. Increasing new PTMs have been reported due to the development of high-resolution mass spectrometry (MS), such as acetylation (Kac), succinylation (Ksucc), propionylation, butyrylation and crotonylation etc [2][3][4]. With bioinformatics tools, their biological processes regulation and metabolic pathways adjustment roles have been illustrated to some extent [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing new PTMs have been reported due to the development of high-resolution mass spectrometry (MS), such as acetylation (Kac), succinylation (Ksucc), propionylation, butyrylation and crotonylation etc [2][3][4]. With bioinformatics tools, their biological processes regulation and metabolic pathways adjustment roles have been illustrated to some extent [2][3][4]. To data, more than 400 distinct PTMs have been reported in living various organisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent study suggested that nuclear acid-based genomic data did not fully consist with proteomic data ( 5 ). Current proteomic analysis afforded a new paradigm for understanding cancer biology with functional context to interpret genomic data ( 6 ). Thus, it is critically important to profile specific biomarkers to distinguish COAD and READ for better understanding of these two diseases and supporting the tailoring of medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With the advanced mass spectrometric technology developed, new PTMs on CDK5 including glycosylation, phosphorylation, ubiquitin, sumoylation and acetylation were identified to play important roles in tumorigenesis [75][76][77]. These PTMs are found to be essential for modulating the activity of CDK5 during tumor occurrence and development.…”
Section: Various Types Of Ptms On Cdk5mentioning
confidence: 99%